Aplikasi Mikoriza Pada Tanah Limbah Pengeboran Minyak Terhadap Beberapa Varietas Cabai - Mizan Maulana; Rika Yusli Harta; Darmadi Erwin Harahap (Universitas Teuku Umar, 2023)
Petroleum waste generated by oil, gas and geothermal business or activities or other activities that produce petroleum waste is a hazardous and toxic waste that has the potential to cause pollution or environmental damage. To restore land contaminated with petroleum, endemic microbes such as mycorrhizae are needed. The recovery process of polluted soil fertility is highly dependent on the quantity of oil spilled and the potential for bioremediation by microbes in the polluted area. The research was carried out at the Experimental Garden of the Faculty of Agricultural and Animal Sciences UNIKI, the Aceh Agricultural Technology Study Laboratory, the Horticulture Laboratory, and the Soil Biology Laboratory, Faculty of Agriculture, Syiah Kuala University, Darussalam Banda Aceh. This research was carried out from March to June 2022. Varieties had a very significant effect on stem diameter 15 DAP, wet root weight 110 DAP, number of fruit planted 110 DAP, fruit dry weight at 110 DAP, significantly affected plant height 15 DAP, stem diameter 30 DAP. and plant weight of 110 DAP. The best chili plant growth was found in the Lado variety and the best chili yield was found in the PM 999 variety. There was an insignificant interaction between chili varieties and mycorrhizal types on the growth and yield of chili plants on the waste soil.